Cleavage of SARS-CoV-2 spike protein mutants - Hoffmann, Markus; Arora, Prerna; Anzhalika, Sidarovich; Graichen, Luise; Hörnich, Bojan; Hahn, Alexander; Pöhlmann, Stefan (Dryad, 2022)
Several SARS-CoV-2 variants emerged that harbor mutations in the surface
unit of the viral spike (S) protein that enhance infectivity and
transmissibility. Here, we analyzed whether ten naturally-occurring
mutations found within the extended loop harboring the S1/S2 cleavage site
of the S protein, a determinant of SARS-CoV-2 cell tropism and
pathogenicity, impact S protein processing and function. None of the
mutations increased but several decreased S protein cleavage at the S1/S2
site, including S686G and P681H, the latter of which is found in variants
of concern B.1.1.7 (Alpha variant) and B.1.1.529 (Omicron variant). None
of the mutations reduced ACE2 binding and cell-cell fusion although
several modulated the efficiency of host cell entry. The effects of
mutation S686G on viral entry were cell-type dependent and could be linked
to the availability of cathepsin L for S protein activation. These results
show that polymorphisms at the S1/S2 site can modulate S protein
processing and host cell entry.
Keywords: FOS: Biological sciences